Epididimal Cyst in Children: A Single-Institutional Experience - Varlikli, Onursal; Akay, Mustafa Alper; Metin, Semih; Cankorur, Mehmet Akif; Anik, Yonca (Urology Journal, 2025)
Purpose: Simple epididymal cysts (EC) are rare in childhood and are mostly diagnosed at puberty. Although there is no consensus on the treatment, a conservative approach is generally preferred. To evaluate patients diagnosed with EC at our clinic in terms of presenting symptoms, diagnosis, and treatment methods. Materials and Methods: Data of patients treated for epididymal cysts at our institution between March 2012 and March 2023 were retrospectively analyzed in terms of age, symptomatology, diagnostic method, treatment method, and outcomes. In all cases, the diagnosis of EC was based on physical examination with scrotal ultrasonography (US) confirmation. Results: A total of 1829 patients underwent scrotal Doppler US, and EC was detected in 72 patients (10.7%). The median follow-up period of the 43 patients was 21.7 (6-80 months). Of these, 9 were bilateral (12.5%). The mean age of the patients at presentation was 14.8 years. Forty-one patients had scrotal pain, 12 had scrotal swelling, and 19 incidentally had EC. The cysts were between 1.2- 37 mm. Only 3 (4.1%) patients required surgical excision due to persistent pain. Conclusion: EC is a benign lesion, and treatment approaches are usually conservative. Surgical excision is recommended for patients with persistent scrotal pain or an acute scrotum.